2021
DOI: 10.1177/0956797620975779
|View full text |Cite
|
Sign up to set email alerts
|

Harder Than You Think: How Outside Assistance Leads to Overconfidence

Abstract: Cognitive ability consists not only of one’s internal competence but also of the augmentation offered by the outside world. How much of our cognitive success is due to our own abilities, and how much is due to external support? Can we accurately draw that distinction? Here, we explored when and why people are unaware of their reliance on outside assistance. Across eight experiments ( N = 2,440 participants recruited from Amazon Mechanical Turk), people showed improved metacognitive calibration when assistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…The authors consider this result as evidence for metacognition extending beyond the brain and into external memory stores (Stone & Storm, 2021). Similarly, Flanagin and Lew (2023) found that people overestimate their task performance if web-based information is available (see also Fisher & Oppenheimer, 2021). Another series of studies suggests that thinking about trivia questions before searching for the answers online improves later recall than immediately searching the Internet (Giebl et al, 2022).…”
Section: Offloading In Everyday Lifementioning
confidence: 94%
“…The authors consider this result as evidence for metacognition extending beyond the brain and into external memory stores (Stone & Storm, 2021). Similarly, Flanagin and Lew (2023) found that people overestimate their task performance if web-based information is available (see also Fisher & Oppenheimer, 2021). Another series of studies suggests that thinking about trivia questions before searching for the answers online improves later recall than immediately searching the Internet (Giebl et al, 2022).…”
Section: Offloading In Everyday Lifementioning
confidence: 94%
“…In contrast, when help is always provided children may be less encouraged to self‐reflect about the quality of their knowledge since the help is available regardless of whether it is needed. Indeed, research in adults demonstrates that actively choosing when to seek help, as opposed to always being provided help, decreases over‐confidence during memory judgments (Fisher & Oppenheimer, 2021). In addition, research in children demonstrates that 5‐ to 6‐year‐olds can improve their metacognitive skills under contexts that scaffold self‐reflection (e.g., when provided with feedback; van Loon & Roebers, 2020), suggesting the children can flexibly enhance their metacognitive ability as a function of experimental contexts.…”
Section: Methodsmentioning
confidence: 99%
“…One line of research to emerge from such studies shows that the coupling of the human mind with digital devices can result in a conflation between internal and external knowledge – people erroneously believe they possess, in their own heads, information from the web (Fisher & Oppenheimer, 2021a). Moreover, ostensibly because people conflate/misattribute the source of knowledge, they think more highly of themselves after searching the web than after not searching the web.…”
Section: Searching the Web Increases Cognitive Self-esteem (Cse)mentioning
confidence: 99%